Association between Clinical Simulation Design Features and Novice Healthcare Professionals' Cognitive Load: A Systematic Review and Meta-Analysis. (October 2022) - Lapierre, Alexandra; Arbour, Caroline; Maheu-Cadotte, Marc-André; Vinette, Billy; Fontaine, Guillaume; Lavoie, Patrick
Background: Clinical simulations are complex educational interventions characterized by several design features, which have the potential to influence cognitive load, that is, the mental effort required to assimilate new information and learn. This systematic review and meta-analysis explored the associations between simulation design features and cognitive load in novice healthcare professionals. Methods: Based on the Joanna Briggs Institute methodology, a search was performed in five databases for quantitative studies in which the cognitive load of novice healthcare professionals was measured during or after a simulation activity. Each clinical simulation was coded to describe its design features. Univariate and multivariate mixed model analyses were performed to explore the associations between simulation design features and cognitive load. Results: From 962 unique records, 45 studies were included and 27 provided enough data on subjective cognitive load (i.e., Paas Scale and NASA-Task Load Index scores) to be meta-analyzed. In the multivariate analysis for the NASA-Task Load Index scores, each repetition of a simulation using the same scenario resulted in a linear decrease in cognitive load. In contrast, technology-based instruction before or during a simulation activity was associated with higher cognitive load. In the univariate analyses, other features such as feedback and instructor presence were also statistically associated with cognitive load. Regarding the univariate analyses of the Paas Scale scores, simulator type, briefing, debriefing, and repetitive practice were statistically associated with cognitive load. Conclusion: This is the first meta-analysis exploring the relationship between clinical simulation design features and novice healthcare professionals' cognitive load. Although the findings show that several design features can potentially increase or decrease cognitive load, several gaps and inconsistencies in the current literature make it difficult to appreciate how such reciprocity influences novice healthcare professionals' learning. These limitations are discussed and avenues for educators and further research are suggested.